Work stress and its influence on the performance of workers in the metalworking industry - Swany Avilés, Elizabeth (2022)
The present study was carried out with the purpose of verifying if stress is related to the performance of workers in the metalworking industry by identifying the stressors that can cause risk of affecting health, such as physical or mental disability and by therefore poor job performance directly affecting the productivity of the company. The methodology of this research is mixed, non-experimental, and cross-sectional. Direct observation and survey were used as data collection tools, as well as the evaluation methods of the Stress questionnaire of the World Health Organization, International Labor Organization and Work Performance of Williams and Anderson. The results obtained determined that 84% of metalworking workers are exposed to a level of stress, 14% have an intermediate level of risk and 2% in the range of moderate stress. It is concluded that the stressors to which workers are exposed in their work environment are related to their performance, so it is essential to promote the application of hygienic measures that reduce stress and increase the performance of workers.